Pengembangan toolkit standarisasi UMKM katering dan kuliner bagi UMKM food community Bandung - Arry Widodo; Retno Setyorini; Astadi Pangarso; Taufan Umbara; Akhmad Yunan; Yulia Nur Hasanah; Patrick Adolf Telnoni; Rizza Indah Mega Mandasari; Pramuko Aji (Riau Journal of Empowerment, 2022)
The culinary business increasingly attracting new business investors and also increasing the competition because a lot of competitors are entering the culinary business. Innovation is needed to increase the competitiveness of a business. Currently, 48.9% of Micro, Small, and Medium Enterprises (MSMEs) are engaged in the primary sector which focuses on agriculture, fisheries, livestock, and forestry. This emphasizes the important role of MSMEs as a strategic sector in national economic development and distributing development results. The Covid-19 not only impacted large businesses but also the MSME, especially the social restriction policy. Conventionally, MSMEs rely on face-to-face transactions in their transactions but now trading activities are carried out digitally, which has proven to be growing rapidly during the pandemic. However, compared to large businesses MSMEs tend to find it difficult to move from conventional to digital activities. MSMEs need expertise in the development of digital content and the use of an attractive and hygienic toolkit. So, in this community service activity, we propose the development of the MSME Catering and Culinary Standardization Toolkit and the UMKM Food Community as a partner.